Oxidized forms of uromodulin promote calcium oxalate crystallization and growth, but not aggregation - Sakdithep Chaiyarit (2022)
Roles of an abundant human urinary protein, uromodulin (UMOD), in kidney stone disease were previously controversial. Recently, we have demonstrated that oxidative modification reverses overall modulatory activity of whole urinary proteins, from inhibition to promotion of calcium oxalate (CaOx) stone-forming processes. We thus hypothesized that oxidation is one of the factors causing those previously controversial UMOD data on stone modulation. Herein, we addressed effects of performic-induced oxidation on CaOx crystal modulatory activity of UMOD. Sequence analyses revealed two EGF-like calcium-binding domains (65th–107th and 108th–149th), two other calcium-binding motifs (65th-92nd and 108th–135th), and three oxalate-binding motifs (199th–207th, 361st-368th and 601st-609th) in UMOD molecule. Analysis of tandem mass spectrometric dataset of whole urinary proteins confirmed marked increases in oxidation, dioxidation and trioxidation of UMOD in the performic-modified urine samples. UMOD was then purified from the normal urine and underwent performic-induced oxidative modification, which was confirmed by Oxyblotting. The oxidized UMOD significantly promoted CaOx crystallization and crystal growth, whereas the unmodified native UMOD inhibited CaOx crystal growth. However, the oxidized UMOD did not affect CaOx crystal aggregation. Therefore, our data indicate that oxidized forms of UMOD promote CaOx crystallization and crystal growth, which are the important processes for CaOx kidney stone formation.